OTP Generation Algorithm: A Rubik’s Cube Principle Implementation - Bose, S; Chowdhury D, Roy (International Journal of Computer Sciences and Engineering, 2025)
A One-Time Password (OTP) is an auto - generated, string of characters (password) that validates the user to carry out a single transaction or session on digital devices like a Computer, Smartphone, Tablet etc. Various unique techniques underwent implementation time and again for producing an optimal and efficient OTP. In most of the techniques, the OTP generated is of a shorter length and comprised of only letters of English alphabet (a – z, A - Z), digits (0 – 9) and characters like @ etc. In this paper a novel approach for generating One-Time Password (OTP) has been proposed using Rubik’s cube principle based on a 4 × 4 cube in which each box of the cube is labeled with characters present on the keyboard such that when the layers of the cube are scrambled in various ways, it creates a 16 character OTP. This technique using Rubik’s cube have never been applied before to generate an OTP.